An Overview of Patient Safety Culture with the AHRQ - Samsul Bahri; Arifah Devi Fitriani; Jamaluddin Jamaluddin (Newinera Publisher, 2022)
Safety has become a global issue, especially for hospitals. Patient safety culture is a product of values, attitudes, competencies, and behavioral patterns of individuals and groups that determine the commitment, style, and ability of health care organizations to patient safety. The purpose of this study was to determine the description of patient safety culture with the AHRQ model. Quantitative research method with cross sectional. The population of all officers in the inpatient installation of RSUD Dr. R. M Djoelham 156 samples found 61 respondents with simple random sampling technique. The results of the study describe the expectations and actions of managers promoting patient safety by 77.04%, organizational learning by 91.8%, cooperation in units of 93.85% (good or strong culture), open communication by 71.04%, feedback on errors 77.05% (good or strong culture), non-punitive response dimension to errors is 61.20% staffing is 59.01% management support for patient safety efforts is 85.8% cooperation between units is 71.32%, Handsoff work and patient transitions are 59.02% (good enough or moderately cultured), the overall perception of hospital staff about patient safety is 68.86% (good enough or moderately cultured), reporting frequency is 73.22% (good enough or moderately cultured). moderate culture). With the results of this study, it is hoped that RSUD Dr. R.M. Djoelham Kota Binjai is expected to continue, maintain, and develop ongoing patient safety programs and maintain the existing patient safety culture.